2020
DOI: 10.1186/s41235-020-00248-z
|View full text |Cite
|
Sign up to set email alerts
|

Wisdom of crowds and collective decision-making in a survival situation with complex information integration

Abstract: Background The wisdom of crowds and collective decision-making are important tools for integrating information between individuals, which can exceed the capacity of individual judgments. They are based on different forms of information integration. The wisdom of crowds refers to the aggregation of many independent judgments without deliberation and consensus, while collective decision-making is aggregation with deliberation and consensus. Recent research has shown that collective decision-making outperforms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…The second limitation is the method of aggregating individuals' judgments. Although only one majority rule was applied in this study, many previous studies on the wisdom of crowds have discussed different ways to effectively aggregate individuals' judgments for improving group judgments [6], [30][31][32] . Some studies have argued the importance of considering subjective con dence in group judgments [30], [32 .…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation is the method of aggregating individuals' judgments. Although only one majority rule was applied in this study, many previous studies on the wisdom of crowds have discussed different ways to effectively aggregate individuals' judgments for improving group judgments [6], [30][31][32] . Some studies have argued the importance of considering subjective con dence in group judgments [30], [32 .…”
Section: Discussionmentioning
confidence: 99%
“…The second limitation is the method of aggregating individuals' judgments. Although only one majority rule was applied in this study, many previous studies on the wisdom of crowds have discussed different ways to effectively aggregate individuals' judgments for improving group judgments [6], [30][31][32] . Some studies have argued the importance of considering subjective confidence in group judgments [30], [32 .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of group decision-making, Grofman et al ( 1983 ) suggested weighing each individual's inputs based on self-reported confidence of their respective responses, in accordance with the belief that individuals can estimate reliably the accuracy of their own judgments (Griffin and Tversky, 1992 ). More recently, Hamada et al ( 2020 ) designed a wisdom of the crowds study that asked a set of participants to rank and rate 15 items they would need for survival and used weighted confidence values to aggregate their inputs. The results were sensitive to the size of the group (i.e., number of participants); when the group was small (fewer than 10 participants), the confidence values reportedly had little impact on the results.…”
Section: Literature Reviewmentioning
confidence: 99%